Public Awareness and Reforms Expected About Various Scams In India That Nurtures Business Environment - J. Anitha and Rishi Nikitha Natarajan (Abhigyan, 2015)
India has been amongst the fastest growing economies in the world in the last decade. It has remained relatively unaffected by the global economic crisis, due to strong fundamentals of the economic policy. However, despite this situation the confidence of international investors and domestic entrepreneurs has been low in the last two years, due to the various scams that have come to light during this period. Corruption in India has taken a high toll in the last few years. News Channels and paper media are both fl with various scams. India needs to deal with the malice of corruption and improve governance. This paper discusses the key media that people use to know about scams, impact of media in revealing scams and in knowing the overall opinion of scams in India. The paper also attempts to identify the major variables that play signifi roles in public awareness of scams. Transformation in terms of economic reforms, judicial reforms, health reforms and agricultural reforms is also discussed with reference to what people look forward to. The study gives major leads to key issues and solutions that need to be addressed to present a healthy business environment in the country